Performance and emission characteristics of ozonated coconut oil in a single cylinder, direct injection diesel engine - Dimapalao, Muhamad-Ali K.
The problem that the world is facing exhibits a domino-effect. Global energy requirement is continually increasing resulting in widespread exploitation of the petroleum-derived fuels which in turn resulted to their depletion and consequently to the sharp increase in their prices in the world market. Globally, there are big issues regarding the excessive emission of many internal-combustion engines such as diesel engines which are big contributors to the air pollution and global warming that promted strictemissions regulations, locally and internationally, for environmental protection and public health concerns.